Why review L. A. Costa Pinto’s concept of structural marginality? - Bôas, Gláucia Villas (Universidade Estadual Paulista / UNESP, 2007)
The article retakes L. de A. Costa Pinto’s critique of the concept of structural marginality, aiming to discuss the ambiguity myth that is present in the debates about the instauration of a modern, competitive and equalitarian order in the country. This work argues that the sociological tradition defined the mixing of traditional, authoritarian and hierarchic behaviors with modern, rational and democratic ones, as an ambiguous way of being almost modern in Brazil. By analyzing the formulation of the structural marginality concept in books such as Lutas de família no Brasil, 1943 and Recôncavo: laboratório de uma experiência humana, 1953, one observes that in spite of promoting positively the understanding of Brazilian society, in a period of transition, its author ends up remaking the myth of ambiguity, through which it is possible to control social changes, recurrently postponing them to a future undetermined period in the future.